Pembentukan Identitas Virtual Generasi Z Pada Penggunaan Akun Kedua (Second Account) Instagram - Netanya Claudine Manuela Pelapory; Augustin Mustika Chairil (Hulondalo Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2026)
This research aims to understand the formation of virtual identity among Generation Z through the use of second accounts on Instagram. Second accounts Instagram provide individuals with a space to showing personal aspects that are not displayed on their primary or first accounts, more formal accounts. The research employs Erving Goffman's Dramaturgical Theory, which explains how individuals perform in their social lives as an actors on a stage. The methodology utilized is qualitative descriptive, involving in-depth interviews with 10 informants who are active Generation Z users of second accounts. The selection criteria for informants include ages ranging from 18 to 24 years and active experience using a secondary account on Instagram. This research is expected to provide new insights into the dynamics of digital identity among Generation Z, as well as enhance the understanding of how social media functions as a platform for self-expression and identity formation. The findings reveal significant differences between the identities presented on first and second accounts. These findings indicate that second accounts on Instagram serve as an important medium for Generation Z to explore their identities within social media.